A New Exploration of "Fell Problem" in Active Galactic Nuclei I——Preliminary Consideration - 魏春艳 程福臻 尤峻汉 黄卫红 KWAN John (中国科学通报：英文版, 1994)
Since the unknown emission features in the spectrum of quasar 3C 273 have beenfirst identified as the blended Fell multiplets, many papers have contributed to thetheoretical and observation research of Fell emission in the spectra of Seyferts andquasars. Usually, optical FeII emission lines are produced by transitions from a